Theoretical investigation on electronic structure and stability of some inverted cucurbiturils by density functional theory. Issue 2 (1st February 2019) - Sin, Kye-Ryong; Ko, Sun-Gyong; Kim, Chol-Jin; Kim, Hyon-Chol; Son, Mun-Ho
ABSTRACT: Structure and stability of diastereoisomers of cucurbit[n]urils (CB[n = 5–10]), the inverted CB[n]s, were investigated by density functional theory (DFT) computations. All the inverted CB[n]s were less stable than their normal CB[n]s and the mono-inverted ones with one inverted glycoluril unit in their structures were more stable than their doubly-inverted isomers. Relative change in dipole moments and molecular electrostatic potentials (MEP) were discussed with the deformation in geometric structure and charge distribution of the normal and inverted CB[n]s. Graphical Abstract: